Channaveera Kanavi - (:unkn) unknown (My University, 2022)
“Nature’s own poet” Chennaveera Kanavi is a great poet who connects us to the love and beauty of nature. He has contributed the best lines on nature in Modern Kannada Literature. His poetry narrates the social-cultural and political transition and ambiguities of society. He was born on 28 June 1928 in North Karnataka, Homballa (Gadak- Dist.). He was brought up by Sakkareppa and Parvatavva at Shirunja village. His father was a primary school teacher and that’s where he spent his early childhood. He recalls how a single teacher used to run the entire school in those days. He did his further studies from Garga. His childhood was the time when the freedom movement was at its peak. The events that were taking place put a deep imprint on his mind. He remembers how there used to be Prabhat Pheris and a cleanliness drive to aware people. He was a very studious child, after securing first in Mulki (7th std), he shifted to Dharwad. He joined RLS High school and stayed at Muruga Mutt’s Prasad Nilaya for the next 4 years. The environment in Mutt was more spiritual than religious. Reciting Vachnas and attending discourses rendered by great scholars and literary giants were in their day-to-day schedule. Since every great personality who visited Dharwad used to visit Mutt this helped him to gain interest in Vachanas. After Matriculation in 1946, he joined Karanataka College Dharwad. This is the place where came in contact with many reputed scholars like D R Bendre, V K Gokak, etc. He recited his first poem “ From imprisonment to freedom” on the auspicious occasion of Indian Independence in the huge public gathering at Dharwad College. This poem expressed the joy of people and tells how their dream has been realized. It got published in college magazines as well as popular newspapers like Jeevana, Jayanti, and Jaya Karnataka. This is how his name got introduced into the history of Kannada Literature. Vidyavardhaka Sangha of Dharwad was the literary and cultural center form many poets, writers, orators, and artists. Many eminent literary personalities used to have their discourse over there. Dharwad had been the land where rural and urban cultures co- existed. Kavyakashi Kanavi’s first collection of his poems got published in 1949. Dr. Bendre himself contributed the preface of the same. It was the era of Modern Literature. Renowned writers like Bendre, Masti, Pu. Ti. Na used to be the observer for the upcoming writers. Within a year his second collection Bhavajeevi got published. It was a long narrative of 580 lines and the preface was written by V K Gokak. This Semi- biographical writeup was much influenced by how the rural lifestyle that he was born and brought up in played a key role in transforming him into a poet. It mentions how Dharwad has a long-lasting impression on his life He started a forum Kavyanubhava Mantapa while being a student. There were good friends and critics Keerthinath Kurthokoti, Shankar Mokakshi Punekar, Vasanth Kauli, Doddamani, and Basavaraj Kattimani, who stayed in Dharwad for some years. All the members of Kavyanubhava Mantapa has left behind a great impression on Kannada Literature. In 1950 he joined Karnataka University for PG. He was married in 1952 to Santa Devi. His writing Madhu Chandra records the pure love of a Samsara or a grihastha. In 1952 he was selected as Secretary of the publication department at the University. He says there are three major impacts of education- first teaching up to higher education (degree level), Research is a very important aspect, and whatever has been researched is to be published. MM Kalburgi ex VC KU Hampi says not only Kannada literature but even the publication house of KU is very thankful to him. He was a great organizer and always invited remarkable personalities who would help him in executing his noble ideas. For around 3-4 decades he took care of the publication section of the university. Those were hay days for the publication house of Karnataka University as number of the worthy publication came to being. He went to many places and people to promote the books and spread the joy of reading. Around 150 lecture series were published during his time. Gurulinga Kaapase literary critique infers how beautifully he writes about nature. Grate Govindaraj shares how in Kanavi’s early writings influence of Bendre, Kuvempu, and Madhura chenna can be seen. Dr. G S Shivarudrappa (Rashtra Kavi - national poet ) also praises the writing style of Katavi. He says that the mind of Kannavi is so pure that even in this modern times his work reflects harmony and peacefulness. From the shadow of Bendre he encountered many poets like Sharma. His specialty is that he retained his originality against all the odds and contributed substantially to Kannada literature. No doubt modern literature brought changes in the thought process. However, Kannavi’s view was to take the new ideas objectively by not succumbing to them wholly. But Kanavi was forced to incorporate irony into his writing which was not in his earlier works. The most influential poets of this period were Ram Chandra Sharma, Gopal Krishna Adiga, Ramanujan, and others. According to cultural critic, Dr. Narahalli Balasubramanya Kanavi’s writeup is based on contemporary issues and it mirrors the corruption of the time. He portrayed the confusion and turmoil of the world and also how it influences mankind. Moreover, like other writers, he doesn’t get disoriented because of Navodaya. In modern literature, we find cynicism, sarcasm, and disillusionment. But in his writing, we can see hope, the hope which is not untrue or far-fetched rather based on reality. He survived the turbulence of modern times and retained his originality. At this conjuncture, he published Deepadhari, persistent in his love for nature respect for values, and philosophical perceptions. His style of writing is a culmination of a balanced proportion of old and modern poetry forms. He forms a bridge between romantic and modern writing. His poetry collection Kaala (Time) has an eminent contribution to modern literature. He talks about the complexities of Human being and their selfless nature of exploitation. In which he says no matter what humans cant harness time. Time has another connotation which is death and a humbling factor too. He denies the idea of calling him Samanvya / Bandaya / Dalit Poet. He says that the formation of the poem is based on reciprocity it means the integration of your feelings and intelligence. So reciprocity relation is a must in the life of the poet. In this Modern period of Literature, Kanavi is one of the only poets who use Sonnets extensively. Moreover, he gave sonnet such flexible form to get acceptability in Kannada literature. He loves using sonnets where there is a blend of perception and intelligence. Writing sonnets to him is like sculpting without altering the form. He strongly believes that it gives him creative liberties without altering the basic flow. In his 14 lines of poetry on Lal Bahadur Shastri. He beautifully portrays the simplistic approach to the life Shastri had He reminds us how Shashtr being in such a high position never thought about wealth. He was a man of character and never shed off. He always spread the helping hand and sacrificed all his needs. He wanted peace and dealt with the Indo-Pak conflict peacefully. Though he had to lose his life. He asks us to ponder what kind of Indian he was? His collection of critics can be read in his 3 books: Chintana 1966, Kavyanusandaha (1970), and Samahita (1977). He had been awarded several academic awards including Sahitya Academy Award and conferred as Nadoja by Karnataka University. He is seen to chair many academic functions worldwide. His specialty is to connect real-time issues to the general public by keeping the originality intact. So he had raised several political issues. In almost all his collections numerous sonnets is found. Through the means of his sonnets, he portrays the people he admires like Gandhiji and Shashtri Ji. Kanavi’s contribution to modern Kannada literature is quintessential. He derived a new way for literature and created a conducive domain for the upcoming poets. The best part is though he had been through various movements known of them deviate his writeup from his originality. Through his artistic articulation by means of the sonnet, he has set an example in expanding the horizons of human relations. He unquestionably has amazing inputs in sculpting modern Kannada Literature. He will always be known for his unique incorporation of bridging cultural ethos to the Modern Era through his writings.
Keywords: Channaveera Kanavi; kavyanubhava mantapa; Kavyakshi; Sahitya chinthana; Pampa Prashasthi awardee; Kannada